HUBUNGAN TINGKAT STRES DENGAN KUALITAS HIDUP PASIEN KANKER PAYUDARA PADA BERBAGAI TINGKATAN STADIUM - Fahira Septilia; Darwin Karim; Nurul Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Breast cancer is a disease of malignant neoplasm derived from cells parenchym. Breast cancer patients can experience various problems wich physical and psychological.This study aims to determine the relationship between stress level and quality of life of breast cancer with descriptive correlation research design and cross sectional approach. There were 30 people taken as the samples of this research. They were taken based on the inclusion criteria using purposive sampling technique. The measuring tools used were questionnaire of Depression Anxiety Stress Scale and questionnaire of quality of life from WHOQOL-BREF. The analysis used were univariate analysis to know the frequency distribution and bivariate using Kolmogorov-Smirnov. The results showed that 1 out of 8 respondents low stress level having low quality of life (12.5%), 7 respondents medium stress level with medium quality of life (85.7%), 3 of 15 respondents high stress level having low quality of life (20.0%), 12 respondents high stress level with medium quality of life (80.0%), 5 of 7 respondents low stress level having low quality of life (71,4%) and 2 respondents very stressful level having medium life quality (28,6%). Based on the result of statistical test using Kolmogorov-Smirnov, which resulted in p value = 0,000 <  (0,05), it can be concluded that there is correlation between stress level with quality of life of breast cancer cancer to the various stage levels. Keywords: Breats Cancer, Stress Level, Quality Of Life